OF THE NECESSARY CHANGE IN THE APPROACH OF ODR MECHANISMS IN BRAZIL (IN TIMES OF PANDEMIC) - do Vale de Almeida Guilherme, Luiz Fernando; Guerra Filho, Willis Santiago (Revista Inclusiones, 2021)
In a scenario of global crisis motivated by an illness that affects everyone, some healthy feedbacks can still be extracted. The legal environment - more specifically in the ways of resolving out-of-court disputes - must be concern with the resolution of conflicts using online channels. This form of distribution of justice already shows significant results mainly outside Brazil and its adoption in a more acute way is essential also in this country